Iron Promoted Ring Opening and Ring Closing Cascade (ROCC) Reaction of Ortho‐Carboxy‐Isoxazoles Leading to Isoindolinone Derivatives. Issue 37 (1st October 2021) - Gudipati, Ramakrishna; Jayaram, Vankudoth; Raghavulu, Karri; Bhoot, Dinesh; Basavaiah, Keloth; Yennam, Satyanarayana; Behera, Manoranjan
Abstract: An efficient and convenient route for the synthesis of various functionalized 3‐alkylidene isoindolin‐1‐ones is presented. The synthesis involves the ring opening and ring closing cascade (ROCC) reaction of ortho ‐carboxy‐isoxazole using Fe/NH4 Cl. This is the first report for the synthesis of 3‐alkylidene isoindolin‐1‐one using Fe/NH4 Cl. Abstract : An efficient and convenient route for the synthesis of various functionalized 3‐alkylidene isoindolin‐1‐ones is presented. The synthesis involves the ring opening and ring closing cascade (ROCC) reaction of ortho ‐carboxy‐isoxazole using Fe/NH4 Cl. This is the first report for the synthesis of 3‐alkylidene isoindolin‐1‐one using Fe/NH4 Cl.